Communication Costs, Direct Flights and International Trade - Taiji Furusawa; Chang Sun; Heiwai Tang; Jiaxu Zhang (CESifo GmbH, 2024)
We build a general equilibrium model of endogenous communication, quality control and trade. We derive a structural gravity equation from the model and show that exogenous communication costs raise the costs of quality control and have a larger impact on products with a lower elasticity of substitution. In our empirical application, we estimate the impact of direct flight connectedness on communication costs using the gravity equation. We overcome the identification challenge using an instrumental variable constructed based on the discontinuity of direct flights at around 6,000-mile distance due to air travel regulations. We find that air connectedness increases trade, especially for products with a low elasticity. We combine the empirical estimates and our equilibrium model to quantify the aggregate impact of air connectedness.
Keywords: F10; R40; 330; international direct flights; elasticity of substitution; face-to-face communication